Cirkulationsplatser - Dunér, Fredrik (2008)
The purpose with this final thesis has been to study the aesthetics and design of roundabouts and to ascertain important factors that influence the experience of them. The investigation was carried out through literature-, field studies and interviews with persons that in different ways have participated in the formation of roundabouts. Furthermore, six roundabouts have been explored in more depth so that the survey would get a more practical link. These six roundabouts all occur in the rim of a city and do thereby have an important role as a gateway. The environments in such contexts are often complex which adds additional difficulty in achieving a visually appealing design, especially when taking into account the usually high traffic intensity. As part of the exploration process a schematic proposal for redesigning a roundabout in the outskirts of Malmo has been performed.